Antinociceptive Activities of Aqueous and Ethanol Extracts of Piper betle Leaves in Rats - Arambewela, L.S.R; Arawwawala', L .D .A .M; Ratnasooriya, W.D (My University, 2005)
Leaves of Piper belle Linn (Piperaceae) possess a broad spectrum of pharmacological and therapeutic properties. However, its antinociceptive activity has not been investigated so far. The aim of this study therefore, was to examine the antinociceptive activity of hot water extract (HWE) and cold ethanol extract (GEE) of P. betle leaves using rats and three models of nociception (tail flick, hot plate, and fonnalin tests). Different concentrations of HWE (125, 200, 300, 500mg/kg) and CEE (125, 200, 300, 500mg/kg) were made and orally administrated to rats, and the reaction times were determined. The results showed that the extracts have marked antinociceptive activity when evaluated in the hot plate and the formalin tests but not in the tail-flick test. The overall antinociceptive effect of CEE was higher than that of HWE. The antinociceptive effect was mediated via opioid mechanisms.